e-Certificate: Online Platform for Certificate Management System - AHMAD RASHIDI, NUR KHALIS (IRC, 2020)
With the wide expansion of technological advancement in the current world where educational institutions such as schools are not excluded of being affected by it, it is critical to have a reliable school management system implemented that helps to ease the process of documentation which involves several parties such as teachers and students. Realizing that most of the schools in Malaysia are well-equipped with computers, it can be a good platform for the implementation of web-based application software which focuses on the system of certification generation. This paper proposes a system for automated certificate generation system for the utilization of teachers as well as school students are to receive their certificate on-line rather than in paper-based form which causes high costs of production. The paper will further elaborate the advantages and importance of having a centralized certificate database in order to combat problem faced by school’s managements such as a huge number of certificates to be produced manually take took up to almost 1000 certificates of students in a year. The most suitable methodology to be used in the development of this project is Rapid Application Development that mainly focuses on Rapid Prototyping. Therefore, e-Certificate system is expected to be the most effective solution to overcome issues in certificate generation.